Ultraflexible, freestanding nanomembranes based on poly(ethylene glycol) - Meyerbröker, Nikolaus; Zharnikov, Michael (Advanced materials, 2014)
Extremely elastic and highly stable nanomembranes of variable thickness (5-350 nm) made completely of poly(ethylene glycol) are prepared by a simple procedure. The membranes exhibit distinct biorepulsive and hydrogel properties. They offer new possibilities for applications such as supports in transmission electron microscopy, matrices for inorganic nanoparticles, and pressure-sensitive elements for sensors.
Gesehen am 29.07.2020